Augustine beyond the book : intermediality, transmediality, and reception - Pollmann, Karla; Gill, Meredith Jane. (Leiden ; Boston : Brill, 2012)
This interdisciplinary collection of essays investigates the processes by which Augustine of Hippo's writings were re-invented in other media, including the visual arts, drama and music. Thereby it highlights the crucial role of Augustine's readers in constructing his universal stature.
The Antipodeans and Science-Faith Relations: The Rise, Fall and Vindication of AugustineBeyond the Books of Augustine into Modern Psychotherapy; Bibliography; Index Nominum et Rerum.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 600
Keywords: Augustine, -- of Hippo, Saint, -- 354-430 -- Congresses; Augustine, -- Saint; Augustine, -- Saint, Bishop of Hippo; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Electronic books; Conference papers and proceedings